Phase 2 trial of neoadjuvant docetaxel, oxaliplatin, and S‐1 for clinical stage III gastric or esophagogastric junction adenocarcinoma - Yukinori Kurokawa; Tomono Kawase; Atsushi Takeno; Haruna Furukawa; Ryo Yoshioka; Takuro Saito; Tsuyoshi Takahashi; Toshio Shimokawa; Hidetoshi Eguchi; Yuichiro Doki (Annals of Gastroenterological Surgery, 2023)
Abstract Background Although perioperative treatment has been the standard of care for resectable gastric cancer in the West, postoperative adjuvant chemotherapy is still the standard in Japan. We conducted the first phase 2 trial to investigate the efficacy and safety of neoadjuvant docetaxel, oxaliplatin, and S‐1 (DOS) chemotherapy for cStage III gastric or esophagogastric junction (EGJ) adenocarcinoma in Japan. Methods Eligibility criteria included cStage III adenocarcinoma of the stomach or EGJ. Patients received docetaxel (40 mg/m2, day 1), oxaliplatin (100 mg/m2, day 1), or S‐1 (80 mg/m2, days 1–14) during a 3‐week cycle. After two or three cycles of DOS, patients underwent surgical resection. The primary endpoint was progression‐free survival (PFS). Results Between June 2015 and March 2019, 50 patients were enrolled from four institutions. Of 48 eligible patients (37 gastric and 11 EGJ adenocarcinoma), 42 (88%) completed two or three DOS cycles. Grade 3–4 neutropenia and diarrhea occurred in 69% and 19% of patients, respectively, but there were no treatment‐related deaths. R0 resection was achieved in 44 (92%) patients, and the pathological response rate (≥ grade 1b) was 63% (30/48). The 3‐year PFS, overall survival, and disease‐specific survival rates were 54.2%, 68.7%, and 75.8%, respectively. Conclusion Neoadjuvant DOS chemotherapy had a sufficient antitumor effect and tolerable safety profile in patients with gastric or EGJ adenocarcinoma. The survival benefit of a neoadjuvant strategy using our DOS regimen should be validated in phase 3 trials.